Personal success strategies developing your potential! : a handbook - Hensey, Mel (ASCE Press, 1999)
"This handbook for managers and leaders presents strategies used by individuals who have experienced professional success and personal fulfillment. In this volume, the author focuses on the individual and shares strategies that have been successful for him as well as for his clients. Strategies offered are based on recent research and focus on attitudinal or habitual behaviors and are designed to assist individuals in making changes and developing themselves to be more effective and successful."